GAMBARAN PENGETAHUAN DAN SIKAP MASYARAKAT PESISIR MENGENAI PEMBERIAN BANTUAN HIDUP DASAR (BHD) PADA KEGAWATDARURATAN WISATA BAHARI - Ni Komang Suastini Asih; I Gusti Ngurah Juniartha; Gusti Ayu Ary Antari (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
The rapid development of the tourism sector is marked by the increasing number of tourist arrivals each year in a country. As tourism progresses there is also an increase in emergency events, especially in marine tourism such as drowning, decompression, breathing failure, cardiac arrest, hypovolemic shock, and cardiogenic shock. The provision of Basic Life Support (BLS) is very important to be known by coastal communities in providing first aid in the event of emergency marine tourism so that the morbidity and mortality cases can be prevented. This study aims to know the level of knowledge and attitudes of coastal communities regarding the provision of BLS in any events of a marine tourism emergency nearby. This study used a cross-sectional analytic design using proportional stratified random sampling with a total sample of 206 people. The study was conducted in Bunga Mekar Village, Nusa Penida from March to April 2020 using a questionnaire as a measurement tool. Based on the results of the study, is shown that the average score of knowledge of coastal communities is 3.20 or if categorized as being at the level of insufficient knowledge and the average score of attitudes of coastal communities is 3.00 or if categorized as being less favorable. Coastal communities at least needed to be given information and BLS training as an effort to increase knowledge and attitudes in providing first aid in the event of a marine tourism emergency in Bunga Mekar Village, Nusa Penida.